The adoption of digital technologies by public high school educators in Gauteng - Zuma, Mlungisi (University of the Witwatersrand, Johannesburg, 2023)
The prevalence of technology in society is increasing and transforming every aspect of modern-day civilization. Technology has transformed industries and will continue making inroads in every industry that technology can disrupt. In education technology has shown its effect by reforming learning and the teaching processes. Technology is argued to inspire inclusion, reinforce subject learning, boost collaboration, and play a part in increased innovation in both educators and learners. However, technology comes with a lot of challenges that create gaps in access. These gaps are concerned with the discrepancy of technology access and usage, whereby those in underprivileged environments cannot fully access technology due to the absence of infrastructure and resources. Therefore, to ensure the gap between those who have access and those who do not is decreasing, strategies and policies must be put in place to address suchinequality. Although technology use in education is increasing, what contributes to this adoption of technology by educators in the classroom has not been extensively explored in South Africa. This quantitative study aimed to investigate the factors influencing public school educators' adoption of digital technologies in the classroom, focusing on high school educators in Gauteng, South Africa. The Unified Theory of Acceptance and Use of Technology adoption model was utilised as the framework to observe factors influencing public school educators' adoption of digital technologies in the classroom. This study focused on a model that examines the factors influencing individuals' intention to use technology and their actual usage behaviour. The model identified three main factors that directly influence intention: social influence, effort expectancy, and performance expectancy. Additionally, it highlighted two direct factors that impact usage behaviour: facilitating conditions and intention. The associations between these factors and intention and usage behaviour are further influenced by mediating factors such as experience, voluntariness, age, and gender, as suggested by Venkatesh et al. (2003). These mediating factors play a role in shaping the relationship between the main factors and individuals ‘intentions and behaviour regarding technology usage. iii Data was collected using an online survey and the survey was sent to Gauteng educators and 104 educators responded. Both descriptive statistics and inferential statistics were used to analyse the data. Females were at 52.9% and males were at 47.1%. The location of schools where educators were based was 34.6% based in urban areas and 65.4% in townships. Most of the respondents were in the age category of 26-35 years (46.2%), the following category 46-55 years (21.2%), followed by 36-45 years (16.3%), under 25 years (10.6%) and lastly 56 and older years (5.8%). The results from this research study indicated that younger educators tend to utilise more ICT in the classroom when compared to older educators. Furthermore, the results showed that as the educator’s age increases, their frequency of using ICT decreases. Therefore, government representatives, technology leaders in education and school management should propose comprehensive ICT development courses that will equip educators of all kinds with the necessary technology skills to assist them in implementing these technologies in the classroom.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School , University of the Witwatersrand, Johannesburg, 2023
Keywords: ICT Access; ICT Usage; ICT Competence; ICT Skills; Digital Technologies; ICT adoption; UCTD; SDG-8: Decent work and economic growth